Research on Integrating Artificial Intelligence in User Feedback Loops for Dynamically Adjusting Video Game Difficulty - Wu, Hongyu (International Journal of Computer Science and Information Technology, 2026)
Dynamic Difficulty Adjustment (DDA) remains one of the most promising mechanisms for optimizing player engagement in interactive digital entertainment. This research presents an end-to-end framework for integrating artificial intelligence into the player feedback loop to adjust game difficulty dynamically. Current similar models of DDA are usually requiring manual setup for controlling the in-game resources, making the capital cost high to deploy such a model. In this research, a functional prototype is deployed and tested in “Gulltovia”, a mobile card game launched on Appstore. We design a data pipeline that parses raw player event logs from the game, computes session-level metrics such as fail count, adjusted playtime, and button interaction frequency, and uses these as inputs to a hybrid classification system that combines rule-based thresholds with a machine learning model. The trained model is exported to ONNX and executed inside the Unity engine, enabling real-time predictions and conservative difficulty adjustments based on probability confidence.